The procedure for appointing a government in Croatia. Remarks on the background of the government crisis of 2015 - Składowski, Konrad (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The article is devoted to the procedure of appointing the government in the Republic of Croatia. The provisions of the Croatian Constitution define this procedure in a rather narrow scope. In practice, this led to a government crisis after the 2015 elections. A government was finally formed at that time. However, in the course of applying the provisions of the Constitution, there were significant problems related to the interpretation of its provisions. The article brings this issue closer.